2021
DOI: 10.1101/2021.05.07.442998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial-temporal targeted and non-targeted surveys to assess microbiological composition of drinking water in Puerto Rico following Hurricane Maria

Abstract: Loss of basic utilities, such as drinking water and electricity distribution, were sustained for months in the aftermath of Hurricane Maria's (HM) landfall in Puerto Rico (PR) in September 2017. The goal of this study was to assess if there was deterioration in biological quality of drinking water due to these disruptions. This study characterized the microbial composition of drinking water following HM across nine drinking water systems (DWSs) in PR and utilized an extended temporal sampling campaign to deter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 73 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…To produce a snapshot of the virome in drinking water distribution systems, we mined publicly available drinking water metagenomes (Chao et al, 2013; Dai et al, 2020; Douterelo et al, 2018; Garner et al, 2018; Jia et al, 2015; Ma et al, 2019, 2017; Potgieter et al, 2020; Sevillano et al, 2021; Shi et al, 2012; Zhang et al, 2019). Table 1 summarizes the metadata for each study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To produce a snapshot of the virome in drinking water distribution systems, we mined publicly available drinking water metagenomes (Chao et al, 2013; Dai et al, 2020; Douterelo et al, 2018; Garner et al, 2018; Jia et al, 2015; Ma et al, 2019, 2017; Potgieter et al, 2020; Sevillano et al, 2021; Shi et al, 2012; Zhang et al, 2019). Table 1 summarizes the metadata for each study.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the influence of water quality parameters independently from study-specific effects, we focused on the Dai et al (2020) samples, collected from the UK and Netherlands, and the Sevillano et al (2021) samples, collected from Puerto Rico. Both studies found that chlorine was a major determinant of the differences in the microbial community composition (Dai et al, 2020; Sevillano et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations